Forest-based Sectors and Interdependence in the Indian Economy - Chatterjee, N. (Indian Forester, 1976)
Foresters in India have long realised the importance of forestry and forest-based sectors in the national economy. No quantitative information of this interdependence, however, appears to be readily available at present. Apart from its appeal to the professional as a curiosum, this knowledge could be essential in the context of planned economic development as well. In this paper, an attempt is made to empirically analyse the role of forest-based sectors, in value terms, in the different producing sectors of the Indian economy. The theoretical aspects are presented and the results of the analysis are furnished. Lastly, their application in development planning is also discussed in brief.